IMPLEMENTASI PROGRAM WAJIB BELAJAR 12 TAHUN DI KABUPATEN INDRAGIRI HULU - Reni Sabrina; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Indonesian government step in achieving educational equity issues, namely the decree No. 70 of 2014 on compulsory education to 12 years and fund regional Bos, 2015. One of the problems facing the district Indragiri Hulu in the field of education that is not maximal implementation of compulsory education to 12 years. Therefore the Government of Indragiri Hulu district is required to pay attention to school-age children to attend compulsory education to 12 years. The main problems that often arise in the success of compulsory education to 12 years is how the government can ensure that children who have graduated from elementary school continuing education to junior high school and children who have graduated from high school to continue their education to the high school level, facilitating school to children ages schools get a decent education, providing infrastructures as supporting teaching and learning activities in schools. This study aims to identify and analyze the implementation of compulsory education to 12 years and examine the factors that affect the implementation of compulsory education to 12 years in Indragiri Hulu.The concept of the theory that researchers use on is public policy, program and policy implementation according to Edward who said that there are four variables that need to be considered in the implementation of the program, namely: 1. Communication, 2. Resources, 3. Disposition, 4. Bureaucratic Structure.The results showed that the implementation of the program's 12-year compulsory education has not run optimally. It diketahun of resources is not adequate: there is a lack of human resources, financial resources are still inadequate, namely the budget obtained by the Department of Education to implement the program is not sufficient in number, socio-economic condition of society that can not afford that still many parents who economically disadvantaged. This resulted in 12-year compulsory education program is not running optimally in Indragiri Hulu.Keyword: implementation, program, compulsory 12 years